Factors that affect students' motivation in ESL classroom of a private institution / Wan Yusrina Wan Yusuff - Wan Yusuff, Wan Yusrina (2015)
Motivation has long been identified as one of the main factors affecting English language learning (Gardner, 1985). It is one of the important factors that influence English learning achievement. Numerous studies have shown that motivation is positively linked to success in learning the English language or any other second language. Generally, motivation and attitude work together to ensure learners’ successful acquisition of a second language, hence, motivational factors have been identified to examine and explain this connection. This study examined the type of learning motivation (instrumental or integrative) and other factors affecting learners’ motivation to learn English of 40 undergraduate students at one of the private institution in Malaysia known as Kolej Poly- Tech Mara, Kuala Lumpur were involved in this study. A modified motivational survey of 40 items adapted from Gardner’s Attitude/Motivation Test Battery (AMTB) was conducted. This study employed mixed methods of quantitative and qualitative research design and utilized questionnaire together with a semi-structured interview in order to collect data. The main findings show that the students are relatively highly motivated and found to be more “instrumentally” motivated to learn English. This reveals that instrumental motivation is a significant factor among this group of students learning English. A significant positive relationship was found between the students’ attitude and motivation in learning English. Based on this study’s findings, some relevant and useful motivational learning implications are recommended for enhancement and improvement of the students’ motivation. Besides, discussions of findings also focus on the distinction between motivation and motivating and on the implications this could have for the English lecturer. Relevant language improvement programs, events or activities are also discussed in accordance with the students’ language difficulties as communicated in the open-ended questions to increase their motivation in English language learning.